Cissus quadrangularis: A comprehensive review as an emerging biomaterial for periodontal regeneration - H Nilofer Farjana; G. Mohan Valiathan (Journal of Oral Research and Review)
Cissus quadrangularis (CQ) is known for its use as a folk medicine for pharmacological properties such as antimicrobial, antiulcer, anti-inflammatory, antitumor, antihemorrhagic, antiallergic, antidiabetic, and antioxidant properties. It is known for its significant role in fracture healing and bone regeneration. To date, it is safe without any adverse effects when used within normal limits. It contains phytoconstituents such as carbohydrates, phytosterols, flavonoids, triterpenoids, glycosides, tannins, saponins, proteins, Vitamin C, alkaloids, and calcium. The alveolar bone is the tooth-supporting apparatus comprising the alveolar bone proper, cortical bone, crestal alveolar bone, and trabecular bone. Periodontal disease is a polymicrobial host immune-mediated inflammatory disease that destroys supporting structures of the teeth. Periodontal regeneration regenerates the lost periodontal structures. It can be using bone grafts. Periodontal tissue engineering is surging in regenerative medicine. It is a triad that includes cells, scaffolds, and growth factors that help to form newly aligned functional periodontal structures. Plant medicine is an alternative medicine that overcomes the side effects of modern medicine. Plant extracts can be used as bioactive scaffolds for regeneration. CQ can differentiate human-derived mesenchymal stem cells into osteoblast and regenerate bone. This review elaborates on the use of CQ as a bioactive compound for periodontal regeneration.